Nonspecific purulent osteomyelitis of the spine. - Kosul’nikov, S. O.; Besedin, A. M.; Tarnapol’skiy, S. A.; Karpenko, S. I.; Kravchenkо K. V.; Simonova, E. V. (Medicni Perspektivi, 2016)
Recently, in Ukraine a trend to increased incidence of suppurative osteomyelitis of the spine is defined. The main factors contributing to incidence increase is the growth of proportion of population with immunodeficiency and implementation of computer and magnetic resonancetomography in clinical practice. Treatment of suppurative osteomyelitis of the spine should include antibiotic therapy, adequate sanitation of the infectious focus, strict bed rest with exercise therapy. Tactics of surgical treatment combined with antibiotic deescalation therapy with glycopeptide antibiotic – teicoplanin and rehabilitation program which helped to achieve recovery in 23 (37.8%) of patients treated conservatively and in 55 (91%) of the operated patients was proposed.